"The New Harmony" of Ferruccio Busoni's Fantasia Contrappuntistica. Issue 3 (3rd July 2018) - Davis, Colin
ABSTRACT: In Ferruccio Busoni's writings, an important nexus emerges between his general views on contemporary harmony, the theories and practices of Bernhard Ziehn and Wilhelm Middelschulte, and his approach to harmony in his Fantasia Contrappuntistica (1910). Busoni's broader harmonic viewpoint, one he shared with Ziehn and Middelschulte, is characterized by the primacy of melody and the notion of harmony resulting from a renewed interest in polyphony. Various aspects of Fantasia Contrappuntistica are grounded in this viewpoint and are reflective of aesthetic concepts Busoni would more fully articulate in the early 1920s. Central to this discussion is a consideration of the influences that came to bear on the genesis of Fantasia Contrappuntistica and Busoni's harmonic experimentation in creating the work.